THE EFFECT OF BRAND AWARENESS, BRAND IMAGE, AND MEDIA COMMUNICATION ON PURCHASE DECISION IN THE CONTEXT OF URBAN AREA RESTAURANT - Anita, Tiurida Lily; Ardiansyah, Imam (APPS Publications, 2019)
This study aims to determine the effect of brand awareness, brand image, and media communication on customer purchasing decisions in restaurants on urban areas. This research is a case study and was conducted at Gubuk Makan Mang Engking Restaurant. The restaurant has three branches, and all are located in urban areas of Depok, Cibubur and Bekasi of Indonesia. This current study is descriptive and the analysis technique used is quantitative using multiple linear regression analysis. The number of samples obtained (based on the Slovin formula) is 100 respondents. The sampling technique uses simple random sampling. The independent variables in this study are brand awareness, brand image, and media communication, while the dependent variable is purchase decision. The test result shows that brand image and media communication have an influence on purchasing decisions. Meanwhile, brand awareness does not affect purchasing decisions. Keywords: brand image, brand awareness, media communication, decision to buy Penelitian ini bertujuan untuk mengetahui pengaruh kesadaran merek, citra merek, dan komunikasi media terhadap keputusan pembelian pelanggan di restoran di daerah perkotaan. Penelitian ini merupakan studi kasus dan dilakukan di Gubuk Makan Mang Engking Restaurant. Restoran ini memiliki tiga cabang, dan semuanya terletak di daerah perkotaan Depok, Cibubur dan Bekasi Indonesia. Penelitian ini bersifat deskriptif dan teknik analisis yang digunakan adalah kuantitatif dengan menggunakan analisis regresi linier berganda. Jumlah sampel yang diperoleh (berdasarkan rumus Slovin) adalah 100 responden. Teknik pengambilan sampel menggunakan simple random sampling. Variabel bebas dalam penelitian ini adalah kesadaran merek, citra merek, dan media komunikasi, sedangkan variabel terikatnya adalah keputusan pembelian. Hasil pengujian menunjukkan bahwa citra merek dan komunikasi media memiliki pengaruh terhadap keputusan pembelian. Sementara itu, kesadaran merek tidak mempengaruhi keputusan pembelian. Kata Kunci: citra merek, kesadaran merek, komunikasi media, keputusan untuk membeli